2018
DOI: 10.1016/j.cherd.2018.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of mixing performance of helical ribbon mixers for high throughput applications using computational fluid dynamics

Abstract:  98 Helical mixer designs were screened using STAR-CCM+ and HEEDS package  Experimental validation was performed using ERT and torque measurements  Statistical analysis revealed key design features affecting mixer performance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Where, ߛሶ is the shear rate (s -1 ), η is the viscosity (Pa.s), K is the consistency coefficient (-), and n is the power law coefficient (-), whereby the specific K and n values for CMC solution are 0.1215 and 0.784, respectively (R 2 = 0.965) [35].…”
Section: Preparation Of Experimental Fluids and Rheological Charactermentioning
confidence: 99%
“…Where, ߛሶ is the shear rate (s -1 ), η is the viscosity (Pa.s), K is the consistency coefficient (-), and n is the power law coefficient (-), whereby the specific K and n values for CMC solution are 0.1215 and 0.784, respectively (R 2 = 0.965) [35].…”
Section: Preparation Of Experimental Fluids and Rheological Charactermentioning
confidence: 99%
“…Based on the numerical analysis with the use of DEM and the experimental results, Pezo et al [ 35 ] determined a mathematical model in the form of second order polynomial and artificial neural network model describing the quality of mixing in a double-screw mixer. In the paper [ 36 ], Mihailova et al demonstrated using computational fluids dynamics (CFD) that mixer height is a key parameter influencing mixing performance. The influence of some design features of mixing elements on mixing efficiency in cylindrical mixer with use of DEM was presented in [ 37 ] showing, that three bladed mixer has better performance that mixer with two or four blades.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many kinds of mixing equipment and methods were developed to promote laminar mixing. A large impeller like helical ribbon impeller is used to improve laminar mixing (Carreau et al, 1976;Furukawa et al, 2013;Kato et al, 2015;Kato et al, 2018;Mihailova et al, 2018). Another method is unsteady mixing method (Murakami et al, 1980;Kato et al, 2005).…”
Section: Introductionmentioning
confidence: 99%